The influence of natural amines on mitochondrial and microsomal cytochrome P-450 enzymes - De Villiers, Etienne Pierre (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbsoch, 1990.